Effects of fetal position on the loading of the fetal brain during the onset of the second stage of labour - Collier, AM; Louwagie, E; Khalid, GA; Jones, MD; Myers, K; Jerusalem, A (American Society of Mechanical Engineers, 2024)
During vaginal labour, the delivery requires the fetal head to mould to accommodate the geometric constraints of the birth canal. Excessive moulding can produce brain injuries and long-term sequelae. Understanding the loading of the fetal brain during the second stage of labour (fully dilated cervix, active pushing, and expulsion of fetus) could thus help predict the safety of the newborn during vaginal delivery. To this end, this study proposes a finite element model of the fetal head and maternal canal environment that is capable of predicting the stresses experienced by the fetal brain at the onset of the second phase of labour. Both fetal and maternal models were adapted from existing studies to represent the geometry of full-term pregnancy. Two fetal positions were compared: left-occiput-anterior and left-occiput-posterior. The results demonstrate that left-occiput-anterior position reduces the maternal tissue deformation, at the cost of higher stress in the fetal brain. In both cases, stress is concentrated underneath the sutures, though the location varies depending on the presentation. In summary, this study provides a patient-specific simulation platform for the study of vaginal labour and its effect on both the fetal brain and maternal anatomy. Finally, it is suggested that such an approach has the potential to be used by obstetricians to support their decision-making processes through the simulation of various delivery scenarios.